Business Development Strategy through SWOT Analysis in Nicesy Donut and Bakery - Febrian, Ihsan Dwi; Asy-Syamil, Muhammad Jahdan; Adi, Rafael Surya; Ramadhan, Iqyan Faiz (Innovation, Technology, and Entrepreneurship Journal, 2024)
This study explores the business development strategy of Nicesy Donut and Bakery through a comprehensive SWOT analysis. Nicesy Donut and Bakery is a well-known bakery in Cilegon, Indonesia with various products and has been established since 2003. The business aims to capitalize on emerging opportunities, such as increasing demand for healthier options and expanding into new markets. This study employs a qualitative approach using interviews with Nicesy Donut and Bakery’s owners and managers between June and July 2024. The analysis highlights leadership, marketing and product management strategies, potential threats, rising ingredients costs and intense competition. Based on the SWOT analysis, strategy and recommendations are provided to enhance the bakery’s market position and drive sustainable growth. This study contributes to the understanding of how small businesses in the bakery industry can utilize strategic tools like SWOT analysis to develop and implement effective business strategies.